The VicHealth Indicators population survey: methodology, prevalence of behavioural risk factors, and use in local policy - Annemarie Wright; Jane Shill; Nikki Honey; Anthony F. Jorm; Bruce Bolam (BMC, 2020)
Abstract Background The Victorian Health Promotion Foundation (VicHealth) is an Australian state-based government agency with a remit to promote health by targeting physical activity, diet, mental wellbeing, tobacco use and alcohol consumption. Population health data is crucial to this work. This paper reports on the measures and methods used in surveillance, examines the prevalence of risk factors in sub-populations and use of risk factor data in local policy and planning. Methods The VicHealth Indicators (VHI) cross-sectional population telephone survey of behavioural and attitudinal health risk factors involved interviews with 22,819 respondents aged 18 years+ from the state of Victoria in 2015. Means or percent prevalences (with 95% CIs) of indicators are presented. Statistically significant differences between the state level and sub-population estimates were deemed to exist when confidence intervals of estimates did not overlap. Use of the data in local policy was assessed through an audit of 77 Municipal Public Health and Wellbeing Plans for 2017-2021. Use in municipal plans according to the municipality's geographical region type and SES was analysed using Welch's ANOVA. Results The average vegetable intake was 2.2 serves per day, far below the national guidelines of 5 serves per day, and only 4 in 10 Victorians were sufficiently active. Young males were twice as likely to be at high risk of alcohol harm compared to the state estimate. Women were twice as likely to feel unsafe walking after dark compared to males. There was a consistent pattern of significantly less favourable results for people living in outer metropolitan areas and a socio-economic gradient was evident for most risk factors. Almost 50% of municipalities used VHI data in their local policy plans. Use of VHI data was significantly higher in high SES municipalities and significantly lower in low SES municipalities relative to the mean. Conclusions The findings indicate the need for continued targeted action on behavioural risk factors, particularly diet and physical activity, and that more intensive policy and practice action is required to address health inequities to ensure that all Victorians can experience good health. Increased support for low SES municipality policy planning may be warranted.